'Who Nigeria Epp?': from muse to text, neo-Marxist appeal and alter/native canonicity of two Nigerian poets. Issue 3 (3rd July 2021) - Adeniyi, Emmanuel
ABSTRACT: This article examines Nigeria as a space where the hopes and aspirations of most of its citizens are occluded owing to the rapacity of individuals who masquerade as leaders in a country once projected as the bastion of the 'Black man' 1 . Tayo Olafioye's The Parliament of Idiots: Tryst of the Sinators and Femi Fatoba's They Said I Abused the Government are examined as illustrations of two alter/native poets who explore Indigenous oral lore to depict the socio-political irrationalities that render Nigeria a locus of anomie. These poets write as public intellectuals using satire and bleak humour to excoriate the country's political leaders, whose avarice is sustained by unending speculation in Nigeria's oil wealth. The poets' collections offer insights into neo-Marxism as a revisionist ideology in Nigeria. While pointing to new lines of social division and undergirding their dystopian reflections, it attenuates the ardour for violent revolution typical of an earlier Marxism. Both poets exhibit a neo-Marxist sensibility in their sardonic portrayal of capitalist acquisitiveness and their excoriation of Nigerian leadership. They taunt the power structures reinforcing inequality, mass poverty and despair in post-independence Nigeria, without seeking to ignite proletarian revolution, offering a form of hope towards a different Nigerian Project.